Code of Ethics - (:unkn) unknown (My University, 1989)
The development of a professional organization and the increasing numbers of people and institutions involved in this function have given rise to the need for a set of organizing principles, an operational code of ethics. With the creation of this statement, the standards for members and for all who would aspire to membership, have been established. The purpose of the Code of Ethics for the National Association of Academic Advisors for Athletics is to avoid confusion in practice, and minimize dispute by, specifying standards of accountability
Keywords: ethics